Profile of Atopic Dermatitis at Dermatovenereology Outpatient Clinic at Tertiary Hospital in Surabaya, Indonesia - Brahmana, Alisha Princessa; Damayanti, Damayanti; Qurnianingsih, Ema; Widia, Yuri (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Atopic dermatitis (AD) is a pruritic skin condition with erythema, lichenified patches, and excoriations from scratching the skin and often affect the patient's quality of life. Patient history and clinical manifestations are key elements in various diagnostic criteria. Therefore, it is important to know clinical profile of AD patients. Purpose: To describe profile of patients with AD at Dermatovenereology Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya in 2019-2021. Methods: This study is a retrospective descriptive study using secondary data from the patients' medical records at Dermatovenereology Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya in 2019-2021. Result: New AD patients in total were 89 patients, dominated by female (53.9%) in age group 2-12 years (37.1%). The most common complaint was itching (83.1%) and trigger factor was unknown (43.8%). Most patients had previous history of atopy (52.8%) and did not know about their family history of atopy (37%). The most common lesion efflorescence was erythematous macule (59.6%) and located on inferior extremity (43.8%). The most frequent systemic therapy was Cetirizine (71.9%) and topical therapy was hypoallergenic emollient (42.7%). Conclusion: Most of AD patients are female in the 2-12 year age group, come with the complaint of itching and do not know the trigger factor, they mostly had previous history of atopy, but they mostly do not know about their family history of atopy, the most common lesion efflorescence are erythematous macules and the location on inferior extremity with the most given therapy are Cetirizine and hypoallergenic emollient.